2017
DOI: 10.5455/javar.2017.d205
|View full text |Cite
|
Sign up to set email alerts
|

Sero-prevalence of toxoplasmosis in sheep and goats in El-Gadarif state

Abstract: Objective: This cross-sectional study was conducted from July to November 2015 to estimate the prevalence of anti-toxopalsma antibodies in sheep and goats in El-Gadarif state. Material and methods: A total of 400 serum samples comprising of 200 sheep and 200 goats were collected and tested by Toxo-latex agglutination test and indirect enzyme linked immunosorbent assay (iELISA). Results:The overall sero-prevalence was 52.0% (n=208/400) using Toxo-latex agglutination test and 45.7%(n=42/92) and 27.2%(n=25/92) us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
2
1
0
Order By: Relevance
“…There is a significant statistical (p<0.05) difference between prevalence and doe age in this study, and this agrees with the findings of several studies that reported that young animals are more vulnerable to T. gondii infections than older animals [31][32][33][34]. This may indicate the dominance of maternally acquired antibodies in the early stage of goats, unless re-infected, lessening antibodies as their age rises [29]. Our findings disagreed with that of Saeed et al [30], who reported that older animals are more susceptible than young animals to T. gondii infection due to continuous exposure to risk factors for a longer period in older animals.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There is a significant statistical (p<0.05) difference between prevalence and doe age in this study, and this agrees with the findings of several studies that reported that young animals are more vulnerable to T. gondii infections than older animals [31][32][33][34]. This may indicate the dominance of maternally acquired antibodies in the early stage of goats, unless re-infected, lessening antibodies as their age rises [29]. Our findings disagreed with that of Saeed et al [30], who reported that older animals are more susceptible than young animals to T. gondii infection due to continuous exposure to risk factors for a longer period in older animals.…”
Section: Discussionsupporting
confidence: 92%
“…Risk factors, such as doe age, presence of cats in and around farms, and gestation period influence the prevalence of T. gondii in goats [28][29][30]. There is a significant statistical (p<0.05) difference between prevalence and doe age in this study, and this agrees with the findings of several studies that reported that young animals are more vulnerable to T. gondii infections than older animals [31][32][33][34].…”
Section: Discussionsupporting
confidence: 89%
“…This result showed clearly the existence of T. gondii infection in sheep and goats in Benghazi and the nearby areas and they are more at risk to T. gondii infection hence the meat from such animals could be a potential risk to public health if consumed raw or undercooked. The latex agglutination test (LAT) is easy to perform, sensitive and has been used for the measurement of antibodies to T. gondii in serum of sheep, goats, pigs, camels, donkeys, humans, and cattle (Al-Ramahi, Hamza and Abdulla, 2010; Younis et al, 2015;Fereig et al, 2016;Atail et al, 2017;Ishaku et al, 2018;Etter, Neves and Tagwireyi, 2019;Julie, Paul and Antoine, 2019). The high overall seroprevalence (55.3%) recorded in this study is consistent with results reported by many authors from different parts of the world (Hove, Mukaratirwa and Lind, 2005;Atail et al, 2017;Etter, Neves and Tagwireyi, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The latex agglutination test (LAT) is easy to perform, sensitive and has been used for the measurement of antibodies to T. gondii in serum of sheep, goats, pigs, camels, donkeys, humans, and cattle (Al-Ramahi, Hamza and Abdulla, 2010; Younis et al, 2015;Fereig et al, 2016;Atail et al, 2017;Ishaku et al, 2018;Etter, Neves and Tagwireyi, 2019;Julie, Paul and Antoine, 2019). The high overall seroprevalence (55.3%) recorded in this study is consistent with results reported by many authors from different parts of the world (Hove, Mukaratirwa and Lind, 2005;Atail et al, 2017;Etter, Neves and Tagwireyi, 2019). These authors recorded an overall seroprevalence of 67.0%, 52.0%, and 83.3% in small ruminants from Zimbabwe, Soudan, and South Africa respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts have been made to isolate the T. gondii tachyzoites from the saliva, urine, vaginal mucosa and nasal secretions of infected food animals [12]. Consumption of products, including milk, from diseased food animals stands as an imperative cause of human infection, which is of concern due to a rise in the consumption of sheep and goat's milk among children with an allergy to cow's milk [13].…”
Section: Introductionmentioning
confidence: 99%